Testing Criteria and Indicators for assessing the sustainability of forest management: genetic criteria and indicators - Namkoong, G.; Boyle, T.J.B.; Gregorius, H.R.; Joly, H.; Savolainen, O.; Ratnam, W.; Young, A. (1996)
This working paper contains proposals for specific genetic criteria and indicators (C&I) which are expected to be part of a more general set of biological C&I. These proposals are intended for use in guiding tropical forest management but the indicators and verifiers we describe are not in the form of simple prescriptions where a single measurement can be recommended for a single causal effect. Since genetic dynamics operate at a different time and spatial scale than the events that can be observed at the level of forest stand effects, a single forest stand event can have effects on several genetic processes. In addition, the pattern of genetic diversity that has already evolved is due to a balance of several evolutionary forces that operate at different spatial and temporal scales and forest practices would therefore be expected to affect several genetic factors. To provide guidance on what genetic processes may be affected by forest practices, we therefore first describe the factors that affect genetic processes and then provide a matrix of relationships between types of forest level events and genetically significant factors. Since the intention of the larger project is to steer possible management actions, the report identifies two main concerns of sustainability: first, whether the genetic variation is being maintained, and second, what conservation or enhancement measures can be effective. We state one criterion and for each of these concerns, sets of indicators are defined that would address the issue of sustainability. For each indicator, sets of verifiers are provided which differ in the biologically relevant feature they measure or in the precision and technical facilities they require. Finally, the need for rapid assessment and precision under difficult field conditions requires research and development of efficient direct and surrogate measures of the genetic resource. We therefore include recommendations for short- and medium term research that would improve the scientific value, cost-effectiveness, ease of use, and further development of genetic criteria and indicators.